Stroke understanding the disease. - Frerichs, Sandra; Garner, Simon; Video Education Australasia ([Bendigo, Vic. : VEA, 2010)
Summary:'In some cases, stroke is a life-threatening medical emergency that leaves the victim with permanent disability. But for many stroke patients, there's a lot that can be done through quick medical attention, good rehabilitation and community support. In this program, two stroke victims take us through their experiences and explain the affects stroke has had on their lives. We speak to experts, including Professor John Olver, Director of Rehabilitation at Epworth HealthCare to help us understand more about the physiology of stroke, what a stroke actually is, the warning signs, symptoms and risk factors.'--Container.
Credits: Commissioning editor, Sandra Frerichs; executive producer, Simon Garner.
Keywords: Cerebrovascular disease -- Patients -- Rehabilitation